Criminal Acts of Sexual Violence Against Biological Children (Case Study at the PPA Unit of the East Lombok Police Criminal Investigation Unit) - Erna Susiawati (Institute Of computer Science (IOCS), 2022)
This study aims to determine the extent of protection provided to children as victims of sexual violence by their families or biological fathers in East Lombok Regency. The analysis that the author does is based on empirical research, seeing how the law actually works in society with an approach to researching the laws and regulations that are used as the basis for legal provisions to analyze this research is empirical legal research that is prescriptive and technical or applied. The research approach uses a law approach and a case approach. The type of research data is secondary data with primary legal materials and secondary legal materials. Data collection techniques in the form of library research and data analysis techniques used are deductive in nature with the syllogistic method. Based on the research, it can be seen that the protection for children as victims of sexual violence by biological fathers has not been maximized as mandated in the Law of the Republic of Indonesia no. 35 of 2014 concerning amendments to Law no. 23 of 2002 concerning child protection. Children who are accompanied by their families tend to be reluctant or refuse the existence of a judicial process for the crimes they have experienced.